Functional recovery in patients with schizophrenia: recommendations from a panel of experts - Guillermo Lahera; José L. Gálvez; Pedro Sánchez; Miguel Martínez-Roig; J. V. Pérez-Fuster; Paz García-Portilla; Berta Herrera; Miquel Roca (BMC Psychiatry, 2018)
Abstract Background The management of schizophrenia is evolving towards a more comprehensive model based on functional recovery. The concept of functional recovery goes beyond clinical remission and encompasses multiple aspects of the patient’s life, making it difficult to settle on a definition and to develop reliable assessment criteria. In this consensus process based on a panel of experts in schizophrenia, we aimed to provide useful insights on functional recovery and its involvement in clinical practice and clinical research. Methods After a literature review of functional recovery in schizophrenia, a scientific committee of 8 members prepared a 75-item questionnaire, including 6 sections: (I) the concept of functional recovery (9 items), (II) assessment of functional recovery (23 items), (III) factors influencing functional recovery (16 items), (IV) psychosocial interventions and functional recovery (8 items), (V) pharmacological treatment and functional recovery (14 items), and (VI) the perspective of patients and their relatives on functional recovery (5 items). The questionnaire was sent to a panel of 53 experts, who rated each item on a 9-point Likert scale. Consensus was achieved in a 2-round Delphi dynamics, using the median (interquartile range) scores to consider consensus in either agreement (scores 7–9) or disagreement (scores 1–3). Items not achieving consensus in the first round were sent back to the experts for a second consideration. Results After the two recursive rounds, consensus was achieved in 64 items (85.3%): 61 items (81.3%) in agreement and 3 (4.0%) in disagreement, all of them from section II (assessment of functional recovery). Items not reaching consensus were related to the concepts of functional recovery (1 item, 1.3%), functional assessment (5 items, 6.7%), factors influencing functional recovery (3 items, 4.0%), and psychosocial interventions (2 items, 5.6%). Conclusions Despite the lack of a well-defined concept of functional recovery, we identified a trend towards a common archetype of the definition and factors associated with functional recovery, as well as its applicability in clinical practice and clinical research.